The effects of oral health and social support on health-related quality of life of migrant older with children in Weifang, China - Jieru Wang; Jinfeng Zhao; Tingting Tian; Xiaoxu Jiang; Hexian Li; Mingli Pang; Fanlei Kong (BMC, 2022)
Abstract Background With the accelerated urbanization and aging population in China, more and more migrant older with children (MOC) moved to new cities. Previous studies mainly explored the acculturation of MOC, yet few focused on the health conditions of this vulnerable group. This study aimed to investigate the effects of oral health and social support on health-related quality of life (HRQOL) of MOC in Weifang, China. Method This study was a cross-sectional study and participants were selected by multi-stage cluster random sampling in Weifang, China. The HRQOL was assessed via the 12-item Short-Form Health Survey (SF-12) which included the mental component summary (MCS) and the physical component summary (PCS). The oral health was evaluated by the Geriatric Oral Health Assessment Index (GOHAI). The social support was administered using the Social Support Rating Scale (SSRS). Descriptive analysis was used to describe participants' sociodemographic variables, oral health and social support. Univariate analysis and binary logistic regression analysis was used to investigate the association between the social support, oral health and HRQOL. Results and discussion It was found that 25.0% of MOC were defined as MCS poor and PCS poor, respectively. Those participants with average and low monthly household income compared to those around them, average and poor oral health, and low levels of social support were more likely to have poor PCS. Those with temporary residence permits, fair and poor oral health, and medium and low levels of social support were more likely to report poor MCS. Conclusion Results indicated that better social support and oral health led to higher HRQOL of MOC. Implications for the government, communities and families of MOC were given to improve their HRQOL.